ROMANIAN FARMER – OWNER, BUSINESSMAN AND ECONOMICAL GOODS CONSUMER - Bucur, Ion; Bucur, Cristian (Economics of Agriculture, 2018)
The transition from command economy to competitive market economy brought the Romanian farmer in three aspects: as owner of land and other goods, producer (businessman) and as consumer of economic goods and services. The Romanian farmer could be considered a beneficiary of transition because he became again owner of the land he had before collectivization of agriculture. He could own an unlimited number of animals and technical means. As owner, the Romanian farmer beside benefits from transition has had losses also. He has not recovered the means of production, which he was forced to take to cooperative, nor the value of them. In a competitive market economy, the farmer is also a business man. He can use his family or he can employ labor resources, he can rent the land or he can associate with other farmers. The farmer initiate, on his own or as associate, business to obtain profit.